My birthday party - Bell, Martin; Day, Christopher ([Melbourne?] : Black Yabby Hotel in association with Dirt Road Publishing House, 2007)
"My Birthday Party is a chronicle of photos, drawings and collages that documents personal domestic space; cubby houses, special occasions, birthdays and places of play both physical and imagined. Its content is personal, rough, ad hoc playful, nostalgic and honest."--publisher website.
Spine title.
"This catalogue was produced to support & document the installation 'Mountains' & the performance 'My Birthday Party' ... Documentary photographs ... by Christopher Day ... [et al.]"--colophon.
"This catalogue was produced to support & document the installation 'Mountains' & the performance 'My Birthday Party' "--colophon.
Keywords: Installations (Art) -- Australia; Performance art -- Australia; Zines